2014
DOI: 10.3389/fcimb.2014.00172
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous response to Coxiella burnetii, the agent of Q fever: the lessons from gene expression analysis

Abstract: The formation of granulomas is associated with the resolution of Q fever, a zoonosis due to Coxiella burnetii; however the molecular mechanisms of granuloma formation remain poorly understood. We generated human granulomas with peripheral blood mononuclear cells (PBMCs) and beads coated with C. burnetii, using BCG extracts as controls. A microarray analysis showed dramatic changes in gene expression in granuloma cells of which more than 50% were commonly modulated genes in response to C. burnetii and BCG. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Incubation of beads coated with C. burnetii phase I or II with mononuclear cells allowed us to investigate the mechanisms of granuloma formation in C. burnetii infection. First, phase II C. burnetii was less efficient than phase I microorganisms in inducing granuloma formation; second, monocytes were more critical than lymphocytes in granuloma formation; and third, granulomatous cells exhibited a transcriptional program that clustered with that of IFN-␥-stimulated macrophages, which are known to be a canonical model of microbicidal cells (255,256).…”
Section: Role Of the Hostmentioning
confidence: 99%
“…Incubation of beads coated with C. burnetii phase I or II with mononuclear cells allowed us to investigate the mechanisms of granuloma formation in C. burnetii infection. First, phase II C. burnetii was less efficient than phase I microorganisms in inducing granuloma formation; second, monocytes were more critical than lymphocytes in granuloma formation; and third, granulomatous cells exhibited a transcriptional program that clustered with that of IFN-␥-stimulated macrophages, which are known to be a canonical model of microbicidal cells (255,256).…”
Section: Role Of the Hostmentioning
confidence: 99%
“…Our results highlight the formation of granulomas in a context of low-diffusion IFN-γ release suggesting a different mode of granuloma formation during C. burnetii infection. Using an in vitro model of granuloma formation, we previously reported that the transcriptional response of C. burnetii -generated granulomas was associated with a down-modulation of genes encoding for T-bet, including IFN-γ ( Faugaret et al, 2014 ). However, the essential role of IFN-γ in granuloma formation is well documented in tuberculosis infection ( Asano et al, 1993 ; Hogan et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was performed as previously described (49). Quantitative PCR was carried out using Light Cycler Fast Start DNA master SYBR Green I kit (Roche) and the primers listed in Table 1 (31). Real-time PCR was performed as follows: initial denaturation at 95°C for 10 min, followed by 39 cycles of denaturation at 95°C for 15 s and an annealing/extending step at 60°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in vitro models of granulomas have been developed by co-culturing peripheral blood mononuclear cells (PBMCs) and Sepharose beads coated with bacterial extracts from Mtb or M. bovis (16, 28, 29). Using this approach, we previously showed that monocytes migrate to the beads, maturate into macrophages which then polarize and fuse to form MGCs under the influence of lymphocytes (30, 31). In addition, we also showed that defective granuloma formation was associated with low TNF-α expression and monocytopenia in septic patients (32).…”
Section: Introductionmentioning
confidence: 99%